Pembuatan Tembaga Sulfat dari Limbah Padat Tembaga dengan Proses Kristalisasi Panas - Tiffanie Dewi Arifilla; Novel Karaman; Lailly Amaretha Kusuma Wardhani (G-Tech: Jurnal Teknologi Terapan, 2024)
The content of this article aims to determine the value of the best crystal formation by hot crystallization using Response Surface Methodology with the Composite Central Design (CCD) method, then the crystals are identified using XRF (X-Ray Fluorescence) analysis. The hot crystallization method at a temperature of 90°C with a stirring speed of 500 rpm was used with variations in reaction time and sulfuric acid concentration. The reaction times used were 50, 55, 60, 65, and 70 minutes, and the sulfuric acid concentrations were 10%, 12%, 14%, 16%, and 18%. The highest mass of copper sulfate crystals obtained was 5.3908 grams with a reaction time of 70 minutes and a sulfuric acid concentration of 18%, with the highest chemical element in the crystal being Cu at 76.06%.